PENGARUH SERVICE EXCELLENT TERHADAP KEPATUHAN FORMAL WAJIB PAJAK BADAN PADA KPP PRATAMA GRESIK - Lenny Jomeiria (Fakultas Ekonomi dan Bisnis, Universitas Airlangga, 2019)
Introduction: The government has launched a program called Service Excellent to improve the quality of service to the community. Through this program, government officials are expected to provide the best service to the community through the skills, attitude, appearance, attention, action and responsibility and coordinated, as well as providingthe best solutions for the needs of the community. In the marketing world, this process is called Service Excellent. One of the government agencies that are running Service Excellent is the Tax Office PrimaryGresik. The Service Excellent formal compliance can affect corporate taxpayers effective Tax Office Primary Gresik.Methods: Service Excellent in Tax Office Primary Gresik can be measured by physical evidence, reliability, responsiveness, assurance and empathy. The technique of collecting data through questionnaires. The analysis method used is multiple linear regression and hypothesis testing to determine the effect formal service excellent adherence corporate taxpayers. Analysis of the data used include validity test, reliability test, normality test, multicollinearity test, heterocedastisity test, autocorrelation test, and hypothesis testing (t test partial and F test simultaneous).Results: The results of this study are variables simultaneously physical evidence, reliability, responsiveness, assurance and empathy influence the formal obedience corporate taxpayers, while only partial assuranceand empathy variables that influence the formal obedience corporate taxpayers.Conclusion and suggestion: Tax Office Primary Gresik should improve and pay more attention about variables simultaneously physical evidence, reliability, and responsiveness to achieve customer satisfactionwith service excellent.